A connection between cognitive ethics and existentialist thinking: The necessary revitalization of emotions - Herrera Guevara, Asunción (Pensamiento. Revista de Investigación e Información Filosófica, 2013)
This paper aims to show the need to link rational components with emotional components with in ethical theories. The first part will show how Kierkegaard and Adorno are two philosophers sensitive to the feelings of single individuals. Suffering is the limit of rational action for these thinkers. With this premise, Kierkegaard and Adorno will rethink their philosophy taking into account the emotional element. In the second part, I will show the need, nowadays, the emotional component to find a solution in bioethical dilemmas.